Avaliação do perfil de células iNKT em crianças com asma severa - Antunes, Liana (2015)
Background: Invariant natural killer T (iNKT) cells play complex functions in the immune system, releasing both Th1 and Th2 cytokines. The role of iNKT cells in human asthma is still controversy and never described in severe therapy asthmatic children (STRA). Objective: To analyse iNKT frequency in peripheral blood of children with severe therapy-resistant asthma (STRA), comparing with children with milder asthma and healthy controls. Methods: This is a case-control study where blood was collected from asthmatic children (n=136) (milder and STRA) and healthy controls (n=40). Peripheral blood mononuclear cells (PBMC) were isolated, stained with anti-CD3 and anti-iNKT (Vα24Jα18), and analysed through flow cytometry. Atopic status was defined by measuring specific IgE in serum. Airway inflammation was assessed through induced sputum. Results: Children with asthma (n = 136) presented an increased frequency of CD3+iNKT+ cells (mean 2.31% SD 4.41), compared to healthy controls (n = 40) (mean 0.48% SD 0.79) (p = 0.02). Mild-asthmatic children (n = 99) showed an increased frequency of iNKT cells (2.65% SD 4.91; p = 0.002) compared to STRA (n = 11) (2.05% SD 1.62). STRA children have shown an increase frequency of iNKT cells (2.05% SD 1.62) than controls (0.48% SD 0.79; p = 0.002). The number of iNKT cells was not different between atopic (n = 127) and non-atopic (n = 45) children. In addition, iNKT cells were not associated with any inflammatory pattern of induced sputum studied classified as eosinophilic (n = 18), neutrophilic (n = 23), mixed (n = 31) (eosinophilic and neutrophilic) and paucigranulocytic (n = 5). However, iNKT cell numbers were not associated with any airway inflammatory pattern (p=0.09) Conclusion and Clinical Relevance: Our data suggested a role to iNKT in paediatric asthma since it increased in asthmatic children; however these cells are not associated with atopic status or with the more severe spectrum of the disease.